Deregulated Rac1 Activity in Neural Crest Controls Cell Proliferation, Migration and Differentiation During Midbrain Development - Gahankari, Apurva; Dong, Chunmin; Bartoletti, Garrett; Galazo, Maria; He, Fenglei (Frontiers in Cell and Developmental Biology, 2021)
Mutations in RAC1 allele are implicated in multiple brain tumors, indicating a rigorous control of Rac1 activity is required for neural tissue normal development and homeostasis. To understand how elevated Rac1 activity affects neural crest cells (NCCs) development, we have generated Rac1CA;Wnt1-Cre2 mice, in which a constitutively active Rac1G12V mutant is expressed specifically in NCCs derivatives. Our results revealed that augmented Rac1 activity leads to enlarged midbrain and altered cell density, accompanied by increased NCCs proliferation rate and misrouted cell migration. Interestingly, our experimental data also showed that elevated Rac1 activity in NCCs disrupts regionalization of dopaminergic neuron progenitors in the ventral midbrain and impairs their differentiation. These findings shed light on the mechanisms of RAC1 mutation correlated brain tumor at the cellular and molecular level.